Pengaruh Pendekatan Metakognitif Terhadap Kemampuan Representasi Siswa Dalam Pembelajaran Matematika SMK Kesehatan Nusantara Kupang - Ryan Nizar Zulfikar (Jurnal Inovasi Matematika, 2019)
The purpose of this study was to analyze the effect of the metacognitive approach on the ability of students to represent mathematics learning. This research is a non-experimental study. The study population was students of Kupang Nusantara Health Vocational School. The sample of this study was the tenth grade students of Kupang Health Vocational School. The method of collecting data collected by researchers is Tests and Interviews,where tests are used to determine students 'mathematical representation abilities and interviews are used to reinforce the test results of students' mathematical representation abilities. The data in this study were tested using the Paired Sample T Test. It can be concluded that learning with a metacognitive approach influences students' representational abilities. This can be proven in the results of the analysis of the Paired Sample T-test. It is known that the average score of the prest-test ability of representation is 12.16 and the post-test ability of students' mathematical representation is 24.73. the conclusion there is a significant influence on mathematical communication skills and students' mathematical representation abilities.